Representasi Budaya Korupsi Dalam Film Ice Cold: Murder, Coffee and Jessica Wongso - Rahmansyah, Brian Yudhistira; Setyo Wibowo, Novin Farid (Communicology: Jurnal Ilmu Komunikasi, 2024)
ABSTRACT Corruption has become a common problem in Indonesia. Corruption in Indonesia has existed since the colonial era and continues, starting from even the smallest level. Even in 2022, the Indonesian NGO Wach Corruption found 579 cases, 1,396 suspects, and state losses of IDR 42,747 trillion, bribes of IDR 693 billion, illegal levies of IDR 11.6 billion, and money laundering of IDR 955 billion. Therefore, this research aims to find out how the culture of corruption is represented in the film Ice Cold: Murder, Coffee and Jessica Wongso. Researchers use a qualitative approach and use semiotic methods, especially John Fiske's codes. The subject used in this research is the film Ice Cold: Murder, Coffee and Jessica Wongso, while the object of this research is the representation of corruption culture in the film Ice Cold: Murder, Coffee and Jessica Wongso. Through the film Ice Cold: Murder, Coffee and Jessica Wongso, Reza Indragiri and Yudi Wibowo succeeded in showing that in Indonesia today the culture of corruption is still very common, such as the bribery case told by Reza Indragiri and Yudi Wibowo's opinion that in Indonesia today everything is about money, which is even Justice can also be bought even by bribing the person concerned.